SNARE-mediated vesicle navigation, vesicle anatomy and exocytotic fusion pore. (July 2018) - Zorec, Robert
Abstract: The focus of this special issue (SI) »Membrane Merger in Conventional and Unconventional Vesicle Secretion« is regulated exocytosis, a universally conserved mechanism, consisting of a merger between the vesicle and the plasma membranes. Although this process evolved with eukaryotic organisms some three billion years ago (Spang et al., 2015), the understanding of physiology and patobiology of this process, especially at elementary vesicle level, remains unclear. Exocytotic fusion consists of several stages, starting by vesicle delivery to the plasma membrane, initially establishing a very narrow and stable fusion pore, that can reversibly open and close several times before it can fully widen. This allows vesicle cargo to be completely discharged from the vesicle lumen and permits vesicle-membrane resident proteins including channels, transporters, receptors and other signalling molecules, to be incorporated into the plasma membrane. The contributions in this SI bring new insights on the complexity of vesicle–based secretion, including discussion that vesicle anatomy appears to modulate exocytotic fusion pore properties and that the soluble N -ethylmaleimide-sensitive-factor attachment protein receptor proteins (SNARE-proteins), not only facilitate pre- and post-fusion stages of exocytosis, but also serve in vesicle navigation within the cytoplasm.